Prevalence of goiter among children aged 8–10 in Binh Dinh province, Vietnam in 2016–2017 - Dat, Truong Quang (AIMS Public Health, 2019)
OBJECTIVE: The study was conducted to estimate the goiter prevalence, and the median urine iodine concentrations among schoolchildren aged 8–10 in Binh Dinh province, Vietnam. METHODS: A school-based cross-sectional survey was carried out from May 2016 to May 2017. A multistage, proportional-to-population-size sampling method with 30 clusters was used. The children were examined by palpation for the presence or absence of goiter based on the criteria of the World Health Organization (WHO), the United Nations Children's Fund (UNICEF), International Council for the Control of Iodine Deficiency (ICCIDD); urinary iodine was determined in microplates by a modification of the Sandell-Kolthoff reaction. The Chi-square test was used to compare prevalences, and the Chi-square test for trend was employed to assess the trend of goiter prevalence and urine iodine levels by age and economic-social areas. RESULTS: 1800 pupils from 8 to 10 years old including 900 males and 900 females were examined and 300 among them were tested for the urinary iodine concentration (UIC). The prevalence of goiter among schoolchildren was 6.6%. The prevalence of goiter tended to increase in areas with disadvantaged conditions, among which the urban areas occupied the lowest prevalence (5%) while the mountainous areas and Midland took the highest (8.8%) (the p-value of 0.0193). The median UIC of the study group was 159.9 µg/L; the 25(th) and 75(th) percentile value was 103 µg/L and 230.2 µg/L, respectively. CONCLUSION: According to the WHO/UNICEF/ICCIDD classification, the goiter prevalence indicated that some regions of Binh Dinh province appeared to be slightly affected by iodine deficiency. These have characterized an important public health challenge, highlighting the need to eliminate iodine deficiency disorders in these areas.